2018
DOI: 10.3892/ijmm.2018.3912
|View full text |Cite
|
Sign up to set email alerts
|

The role of focal adhesion kinase in transforming growth factor-β2 induced migration of human lens epithelial cells

Abstract: The migration of lens epithelial cells towards the posterior capsule is a key event in the development of posterior capsule opacification (PCO). Accumulating evidence has described crosstalk between growth factors and adhesive signaling pathways in wound healing and cell migration. The aim of the present study was to elucidate an aberrant transforming growth factor (TGF)-β2 signaling pathway that regulated the migration of lens epithelial cells in the pathological context of PCO. The expression of fibronectin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Various genes are involved in the migration of LECs [ 19 , 21 , 33 , 34 , 35 ]. We observed an increased expression of MMP9 at 1 and 2 Gy ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various genes are involved in the migration of LECs [ 19 , 21 , 33 , 34 , 35 ]. We observed an increased expression of MMP9 at 1 and 2 Gy ( Figure 6 A).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in MMP9 protein levels has previously been identified following proton irradiation [ 10 ]. Liu et al [ 35 ] showed that an increase in TGFβ2 expression significantly increased migration and that inhibition of PTK2 decreased TGFβ2-mediated cell migration, indicating that both genes have a role in the migration of LECs. In the present study, no significant changes were observed in the expression of PTK2 ( Figure 6 B), suggesting that this gene does not play a role in the changes in migration following low doses of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…ECM is known to acquire substantial changes in composition, structure, and mechanics, which together exacerbate disease etiology through promotion of angiogenesis, cell differentiation, and immune activation (Shelef et al., ). Fn was verified to activate FAK consequently promote HLEC cell migration (Liu et al., ). Our results showed that with STAT3 and NF‐κB pathways inhibitors, the migration rate of RPE cells induced by IL‐2 dropped as well.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor β (TGF β ) and especially TGF- β 2, the major isoform in the aqueous humor of the eye, play a central role in the pathogenesis of PCO [15, 16]. In our study, treatment with TGF- β 2 at a concentration of 10 ng/ml for 48 h was used to stimulate SRA01/04 cells [17, 18], mimicking PCO in vitro.…”
Section: Discussionmentioning
confidence: 99%